Holomorphic Spaces in the Unit Ball of - Augusto Guadalupe Miss Paredes; Lino Feliciano Reséndis Ocampo; Luis Manuel Tovar Sánchez (Journal of Function Spaces and Applications)
We introduce the and vector spaces of holomorphic functions defined in the unit ball of , generalizing previous work like Ouyang et al. (1998), Stroethoff (1989), and Choa et al. (1992). Likewise, we characterize those spaces in terms of harmonic majorants as a generalization of Arellano et al. (2000).